Toward an epistemology of criminalistics: Deconstructing some foundational myths (Research, Society and Development, 2024)
The definition of the nature of criminalistics and forensic science, as well as its principles and postulates, has been the subject of intense debate in international literature. The aim of this work was to analyze some concepts widely accepted in national literature related to the definition of the basic principles of criminalistics and/or forensic science. In the first part of the article, a survey was made of the principles of forensic science and/or criminalistics found in national and international literature. In the second part, the historical consolidation of the principles of criminalistics adopted in Brazil was analyzed. In the third part, the principles consolidated in the national community of forensic scientists were confronted with international discussions on the nature of forensic science and the basic concepts of science and scientific investigation. The international community tends to define forensic science as a science that shares many of the rigorous procedures derived from natural sciences, but which also presents its own postulates and methodologies. Among them, the historical reconstruction of the criminal event, based on rigorous analysis of the traces. Conversely, the principles commonly accepted by the forensic scientist community in Brazil present some important conceptual inconsistencies, as they are based on traditional and empirical knowledge, passed from generation to generation (Cunha, 1987). Thus, certain concepts consolidated in the Brazilian forensic science community seem to go against classical definitions in the field of science. Reviewing these concepts is essential, as ideas are associated with practices and worldviews.